Transferring university knowledge to develop new technologies: the model of the "OncoRay – Joint Center for Radiation Research in Oncology". (17th October 2010) - Gurtner, Sebastian; Lehmann, Claudia; Pieck, Stefan; Schefczyk, Michael; Sauerbrey, Roland; Baumann, Michael
The objective of this paper is to give an insight on how technology and knowledge transfer is incorporated by research facilities. It also shows how the establishment of the "OncoRay Center for Radiation Research in Oncology" fosters the transfer of research activities into commercial products. We provide information on the motivation of the partners, research activities and transfer strategies. The cooperation portfolio as well as structure of the centre is also discussed.